2015
DOI: 10.1186/s13568-015-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl hydroperoxide reductase enhances the growth of Leuconostoc mesenteroides lactic acid bacteria at low temperatures

Abstract: Lactic acid bacteria (LAB) can cause deterioration of food quality even at low temperatures. In this study, we investigated the cold-adaptation mechanism of a novel food spoilage LAB, Leuconostoc mesenteroides NH04 (NH04). L. mesenteroides was isolated from several spoiled cooked meat products at a high frequency in our factories. NH04 grew rapidly at low temperatures within the shelf-life period and resulted in heavy financial losses. NH04 grew more rapidly than related strains such as Leuconostoc mesenteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…1a verifies that protein folding led to a decrease in binding sites for Ag + . Its up-regulated expression in viable cells after TPT degradation further demonstrated alkyl hydroperoxide reductase is an effector protein (Supplementary Table S5 ) for the catalysis of organic hydroperoxides under TPT stress 10 .…”
Section: Resultsmentioning
confidence: 93%
“…1a verifies that protein folding led to a decrease in binding sites for Ag + . Its up-regulated expression in viable cells after TPT degradation further demonstrated alkyl hydroperoxide reductase is an effector protein (Supplementary Table S5 ) for the catalysis of organic hydroperoxides under TPT stress 10 .…”
Section: Resultsmentioning
confidence: 93%
“…Leu. mesenteroides grow at temperatures below 10 °C and is often isolated from meat products stored at low temperatures [ 38 ]. In this study, Leu.…”
Section: Resultsmentioning
confidence: 99%
“…The AhpC belongs to typical 2‐Cys peroxiredoxin (Prx) containing Cys46 and Cys166 (amino acid numbering based on the sequence of in the GenBank with accession number of KM052591) as the active site residues. The former Cys in the N‐terminal is predicted to function as a peroxidatic Cys that is crucial for substrate binding, while the latter Cys in the C‐terminal is a resolving Cys that is responsible for product release . The isolated 1530 bp AhpF gene encodes a polypeptide of 509 amino acid residues with two conserved CHNC and CPHC catalytic residues required for reduction of oxidized‐AhpC during catalytic turnover.…”
Section: Resultsmentioning
confidence: 99%
“…PCC7120 protects E. coli from multiple abiotic stresses, such as heat, salt, pesticide, cadmium, copper, and UV-B [10]. Moreover, in addition to its function as a peroxide reductase, AhpC of Helicobacter pylori also acts as a molecular chaperone preventing protein misfolding under oxidative stress [11] and it has been demonstrated recently that alkyl hydroperoxide reductase enhances the growth of Leuconostoc mesenteroides lactic acid bacteria at low temperatures suggesting AhpC role in cold adaptation [12]. All together demonstrated that the bacterial AhpCs have multifunctional characteristics other than as antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 99%